A robust porous quinoline cage: transformation of a [4+6] salicylimine cage by povarov cyclization - Alexandre, Pierre-Emmanuel; Zhang, Wen-Shan; Rominger, Frank; Elbert, Sven; Schröder, Rasmus R.; Mastalerz, Michael (Angewandte Chemie, 2020)
Porous shape-persistent organic cages have become the object of interest in recent years because they are soluble and thus processable from solution. A variety of cages can be achieved by applying dynamic covalent chemistry (DCC), but they are less chemically stable. Here the transformation of a salicylimine cage into a quinoline cage by a twelve-fold Povarov reaction as the key step is described. Besides the chemical stability of the cage over a broad pH regime, it shows a unique absorption and emission depending on acid concentration. Furthermore, thin films for the vapor detection of acids were investigated, showing color switches from pale-yellow to red, and characteristic emission profiles.